Pain, comorbidities, and clinical decision-making: conceptualization, development, and pilot testing of the Pain in Aging, Educational Assessment of Need instrument - Siaton, Bernadette C.; Hogans, Beth B.; Frey-Law, Laura A.; Brown, Lana M.; Herndon, Christopher M.; Buenaver, Luis F. (Frontiers in Pain Research, 2024)
Introduction: Pain is highly prevalent in older adults and often contextualized by multiple clinical conditions (pain comorbidities). Pain comorbidities increase with age and make clinical decisions about pain treatments complex. We sought to develop a brief survey of healthcare practitioners to assess the impact of medical and mental health conditions, common in older adults and potentially relevant to chronic pain, on the process of clinical decision-making regarding treatment choices.Methods: A mixed-methods approach was used. Scoping review methodology was applied to appraise research literature and selected Medicare-based data. A geographically and professionally diverse interprofessional advisory panel of experts in pain research, medical education, and geriatrics was formed to advise development of the list of pain comorbidities potentially impacting healthcare professional clinical decision-making. A pilot instrument was developed and pilot tested by diverse certified healthcare practitioners from 2 institutions. Respondents were asked to rate their agreement with condition prevalence and impact on clinical decision-making using a 5-point Likert scale. Individual conditions were scored in terms of percent agreement.Results: Scoping reviews indicated that pain conditions and comorbidities are prevalent in older adults but not universally recognized. We identified a gap in the literature regarding what educators need to support the design of pain education modules mirroring older adult clinical complexity. The interprofessional advisory panel identified 26 common clinical conditions for inclusion in the pilot PAEAN instrument. Conditions fell into three main categories: 'major medical', i.e., cardio-vascularpulmonary; metabolic; and neuropsychiatric/age-related. The instrument was pilot tested by surveying clinically active healthcare providers, e.g., physicians, nurse practitioners, who all responded completely. Median time required to complete the survey was less than 3 minutes.Conclusion: This study, developing and pilot testing our 'Pain in Aging -Educational Assessment of Need' instrument suggests that 1) many clinical conditions impact pain clinical decision-making, and 2) surveying healthcare practitioners about whether pain comorbidities impact clinical decision-making in the care of older adults is highly feasible. Given the challenges intrinsic to safe and effective clinical decision-making regarding chronic pain in older adults, and attendant risks, together with the paucity of existing relevant work, much more education and research are needed.